(untitled) (Medical Forum Monthly, 2022)
Objective: To compare anatomical parameters of Lamina cribrosa (LC) with functional ophthalmological characteristics in Primary open-angle glaucoma (POAG) cases and controls. Study Design: Case-control study Place and Duration of Study: This study was conducted at the Al-Ain Eye Institute, Karachi from November, 2018 to February, 2019. Materials and Methods: Expert ophthalmologist selected 57 POAG cases and 46 age-matched healthy controls. Calibration of intraocular pressure (IOP) and open angle was done using Goldmann tonometry and Slit-lamp biomicroscopy with stereoscopic ophthalmoscopy respectively. Highly specific spectral domain ocular coherence tomography (SD-OCT) was used to ascertain the anterior laminar depth (ALD), lamina cribrosa thickness (LCT) and retinal nerve fiber layer thickness (RNFLT). The functional visual field parameters of mean deviation (MD) and pattern standard deviation (PSD) were calculated using Humphrey Field Analyzer. Results: Statistically significant results obtained for MD, with cases the range was -2.92dB ± 2.52 dB and in controls -2.21 dB ± 2.52 dB. Similar high significance shown by PSD, in cases was 7.54 dB ± 4.69 dB, and in controls it was 3.73 dB ± 2.12 dB. Anatomical characteristic of LCT revealed significant reduced measurements in cases (218.07 ± 79.80 µm) as compared to controls (271.77 ± 64.45). RNFLT elaborated alike significantly reduced calibrations in POAG cases (73.21 ± 13.63 µm) which in controls was 78.85 ± 9.01µm. Non-significant results obtained for ALCD. Conclusion: Estimation of anatomical and functional parameters of LCT, RNFLT, MD and PSD may add heavily in diagnosis and prognosis of POAG patients.